2014
DOI: 10.2217/fmb.14.77
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous Hemagglutinin of Bordetella Pertussis : a Key Adhesin with Immunomodulatory Properties?

Abstract: The filamentous hemagglutinin of pathogenic Bordetellae is a prototype of a large two-partner-system-secreted and β-structure-rich bacterial adhesin. It exhibits several binding activities that may facilitate bacterial adherence to airway mucosa and host phagocytes in the initial phases of infection. Despite three decades of research on filamentous hemagglutinin, there remain many questions on its structure-function relationships, integrin interactions and possible immunomodulatory signaling capacity. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 150 publications
0
17
0
2
Order By: Relevance
“…There is both direct and indirect evidence for in vivo expression of the T3SS in B. pertussis. For example, Bsp22 was detected in lung homogenate of B. pertussis-infected mouse (7,44,45). In addition, some clinical isolates that did not produce BteA (one of the effectors of the T3SS) due to an insertion sequence (IS) in the promoter of bteA still secreted BopD and produced a functional T3SS apparatus (21).…”
Section: Discussionmentioning
confidence: 99%
“…There is both direct and indirect evidence for in vivo expression of the T3SS in B. pertussis. For example, Bsp22 was detected in lung homogenate of B. pertussis-infected mouse (7,44,45). In addition, some clinical isolates that did not produce BteA (one of the effectors of the T3SS) due to an insertion sequence (IS) in the promoter of bteA still secreted BopD and produced a functional T3SS apparatus (21).…”
Section: Discussionmentioning
confidence: 99%
“…Filamentous hemagglutinin as a key virulence factor has been reported in both plant and animal pathogens including E. chrysanthemi, B. pertussis , and A. baumannii (Rojas et al, 2002; Astaneh et al, 2014; Romero et al, 2014). In our study, we found that compared to the wild type, TSS fha exhibited a distinct reduction in serum survival, which is the first observation of an association between bacterial FHA and serum resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It is secreted in a Sec-dependent manner by the two-partner secretion (TPS) system, which includes an outer membrane-associated accessory protein interacting with FHA N-proximal secretion domain. Functionally, it has proapoptotic activity and promotes bacterial aggregation (Locht et al, 1993, 2001; Romero et al, 2014). In Xanthomonas axonopodis pv.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fha also appears to act as a suppressor of inflammation in the airways [19,20]. As Fha is a component of acellular pertussis vaccines, this immunomodulatory activity may be a problem for the efficacy of these vaccines.…”
Section: Role and Activity Of B Pertussis Virulence Factorsmentioning
confidence: 99%